Paparan Media Sosial, Gaya Hidup Hedonis, Dan Pengelolaan Keuangan Mahasiswa: Peran Mental Budgeting Di Kota Kupang - Amelia Theofrida Mali; Stanis Man; Engelbertus Gloria Christy Watu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Student financial management is increasingly important because social media exposure and lifestyle-oriented consumption may shape spending decisions. This study examines the effects of social media exposure and hedonic lifestyle on student financial management in Kupang City and tests the role of mental budgeting. A quantitative design was applied to 102 students from three private universities. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and Partial Least Squares Structural Equation Modeling. The findings show that social media exposure was moderately high, hedonic lifestyle was low, financial management was moderately good, and mental budgeting was good. The structural results indicate that social media exposure and hedonic lifestyle did not significantly affect financial management. Mental budgeting had a positive and significant direct effect but did not moderate the relationships between the independent variables and financial management. These findings highlight the practical need for campus-based financial education focused on budgeting discipline, impulse-spending control, and periodic financial evaluation.